Recent progress in competitive intelligence, competitive technical intelligence and knowledge management - Henri, Dou (Revista Ibero-Americana de Ciência da Informação, 2011)
This paper discusses the role of competitive intelligence and knowledge management to create, maintain and sustain competitive advantages. The triple helix model, based on the integration of the public sector (government), business models (private corporations) and universities to promote innovation is examined. Research trends in competitive intelligence are presented. It concludes that the systematic use of the technology monitoring should support the comparison between various business models of companies that hold the market best practices and form a basis to knowledge for the decision making process and strategies development.